2020
DOI: 10.1111/aos.14399
|View full text |Cite
|
Sign up to set email alerts
|

Bimonthly, treat‐and‐extend and as‐needed ranibizumab in naïve neovascular age‐related macular degeneration patients: 12‐month outcomes of a randomized study

Abstract: To assess the noninferiority of the treat-and-extend (T&E) and fixed bimonthly regimens of 0.5 mg intravitreal ranibizumab as compared with the pro re nata (PRN) in na€ ıve patients with neovascular age-related macular degeneration (nAMD). Methods: Phase IV, randomized, 12-month, multicentre trial. Patients aged ≥50 years with nAMD and visual impairment [best-corrected visual acuity (BCVA) between 23 and 78 Early Treatment Diabetic Retinopathy Study (ETDRS) letters] were eligible. Patients (one eye per patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…The In-Eye trial reported a greater mean number of injections and clinic visits with ranibizumab T&E compared with bimonthly dosing over 12 months (injections: 9.3 vs 7.6; visits: 10.4 vs 8.6, respectively; P < 0.001). 33 In the ARIES trial, the early-start T&E arm received approximately one fewer injection over 12 months than the late-start T&E arm. 31 This difference was also reflected over 2 years of the ARIES study, with patients in the late-start T&E arm switching to a T&E regimen in the second year.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The In-Eye trial reported a greater mean number of injections and clinic visits with ranibizumab T&E compared with bimonthly dosing over 12 months (injections: 9.3 vs 7.6; visits: 10.4 vs 8.6, respectively; P < 0.001). 33 In the ARIES trial, the early-start T&E arm received approximately one fewer injection over 12 months than the late-start T&E arm. 31 This difference was also reflected over 2 years of the ARIES study, with patients in the late-start T&E arm switching to a T&E regimen in the second year.…”
Section: Resultsmentioning
confidence: 99%
“…In the In-Eye trial, a mean of 9.3 vs 7.4 injections were administered in the ranibizumab T&E and PRN arms, respectively ( P < 0.001), with a mean of 10.4 vs 13.6 clinic visits over 12 months ( P < 0.001). 33 The number of injections with T&E regimens may decrease in subsequent years; however, a head-to-head RCT comparing T&E with PRN strategies beyond 1 year is not yet available. Seven observational studies comparing T&E with PRN regimens reported more injections over the study period with T&E than with PRN 24 , 36 , 39 43 ; however, of these studies, the 3 that reported number of clinic visits indicated more visits with PRN than with T&E regimens.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations